Toward a protocol for quantifying the greenhouse gas balance and identifying mitigation options in smallholder farming systems - Rosenstock, Todd S.; Rufino, Mariana C.; Butterbach-Bahl, Klaus; Wollenberg, Eva Karoline (IOP Publishing, 2013)
Globally, agriculture is directly responsible for 14% of annual greenhouse gas (GHG) emissions and induces an additional 17% through land use change, mostly in developing countries (Vermeulen et al 2012). Agricultural intensification and expansion in these regions is expected to catalyze the most significant relative increases in agricultural GHG emissions over the next decade (Smith et al 2008, Tilman et al 2011). Farms in the developing countries of sub-Saharan Africa and Asia are predominately managed by smallholders, with 80% of land holdings smaller than ten hectares (FAO 2012). One can therefore posit that smallholder farming significantly impacts the GHG balance of these regions today and will continue to do so in the near future.